2021
DOI: 10.1021/acs.jcim.1c00838
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Key Amino Acids in the Antimicrobial Mechanism of a Bacteriocin Model Revealed by Molecular Simulations

Abstract: The AS-48 bacteriocin is a potent antimicrobial polypeptide with enhanced stability due to its circular sequence of peptidic bonds. The mechanism of biological action is still not well understood in spite of both the elucidation of the molecular structure some years ago and several experiments performed that yielded valuable information about the AS-48 bacterial membrane poration activity. In this work, we present a computational study at an atomistic scale to analyze the membrane disruption mechanism. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Research has shown that the high amino acid content of LAB bacteriocin makes the bacteriocins positively charged at neutral or acidic pH and can be adsorbed on cation exchange columns to separate them from other heteroproteins. 73 The 0.6 mol L −1 NaCl eluted fraction of NCUH062003 showed high inhibitory activity, indicating that this fraction contained the target inhibitory proteins, which were determined by BCA analysis to have a protein concentration of 0.34 mg mL −1 (Fig. 7C).…”
Section: Resultsmentioning
confidence: 93%
“…Research has shown that the high amino acid content of LAB bacteriocin makes the bacteriocins positively charged at neutral or acidic pH and can be adsorbed on cation exchange columns to separate them from other heteroproteins. 73 The 0.6 mol L −1 NaCl eluted fraction of NCUH062003 showed high inhibitory activity, indicating that this fraction contained the target inhibitory proteins, which were determined by BCA analysis to have a protein concentration of 0.34 mg mL −1 (Fig. 7C).…”
Section: Resultsmentioning
confidence: 93%
“…It has a remarkable amphipathic surface where the positively charged residues (helices 4 and 5) are separated from the rest of the hydrophobic or uncharged residues (helices 1, 2, and 3) by a hypothetical plane delimitated by the Cα atoms of 4 glutamic acids (González et al, 2000;Sánchez-Hidalgo et al, 2008. This asymmetrical charge distribution, the stabilizing interaction of tryptophan residues, and the amphipathicity of the molecule play an essential role in the mechanism of action of the peptide (Cruz et al, 2021).…”
Section: As-48 Mechanism Of Action: Minimizing Resistance Developmentmentioning
confidence: 99%
“…Peptides can attach to and penetrate membrane bilayers due to their amino acid composition, amphiphilicity, cationic charge, and side. Natural peptides can disrupt cytoplasmic membrane permeability, inhibit cell wall production, restrict nucleic-acid synthesis, and decrease protein synthesis, causing bacterial cell death (Cruz et al 2021).…”
Section: Antibacterial Activitymentioning
confidence: 99%